1997
DOI: 10.1097/00005768-199705000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a rhinovirus-caused upper respiratory illness on pulmonary function test and exercise responses

Abstract: Upper respiratory illness (URI) may cause more frequent acute disability among athletes than all other diseases combined. The purposes of this study were to determine the impact of a rhinovirus-caused URI on resting pulmonary function submaximal exercise responses and on maximal exercise functional capacity. Twenty-four men and 21 women (18-29 yr) of varying fitness levels were assigned to the experimental group (URI), and 10 additional individuals served as a control group (CRL). An initial serological screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…11 The presence of illnesses such as upper respiratory tract infections (URTIs) is of great concern for team-sport athletes, given their infectious nature and the potential negative influence on performance and wellbeing. 12 Thus, these athletes should be appropriately monitored to identify periods when they are at increased risk of illnesses. 10,13,14 There is limited research describing the influence of factors such as training and competition demands on the incidence of illness in professional team-sport athletes.…”
Section: Introductionmentioning
confidence: 99%
“…11 The presence of illnesses such as upper respiratory tract infections (URTIs) is of great concern for team-sport athletes, given their infectious nature and the potential negative influence on performance and wellbeing. 12 Thus, these athletes should be appropriately monitored to identify periods when they are at increased risk of illnesses. 10,13,14 There is limited research describing the influence of factors such as training and competition demands on the incidence of illness in professional team-sport athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Weidner et al demonstrated the effects of a URTI caused by rhinovirus 16. A wellconducted trial showed no significant difference between those inoculated with the virus versus those receiving placebo at days 2, 5, and 8 in pulmonary function, VO 2 max, and exercise to fatigue [9]. This supports the concept that there are few physiologic changes in the athlete's body during an uncomplicated URTI, and athletes should be considered medically appropriate for return to participation even while symptomatic.…”
Section: Infectious Conditions Of the Lungs And Respiratory Tractmentioning
confidence: 63%
“…This finding adds to a trend that moderate exercise during a URTI does not affect symptom severity or duration. 10 Further, moderate exercise during a URTI does not affect pulmonary function test and exercise responses, 19 running gait, 20 or physical performance. 21 Similar studies with other forms of exercise (for example, weight training), other populations (for example, young and old, labourers), and fitness levels (for example, highly fit) warrant further investigation.…”
Section: Discussionmentioning
confidence: 95%